On the characterization of sandwich panels for solar flat plate collectors’ applications: theoretical and experimental investigation - Djemai Hocine; Hecini Mabrouk; Adnane Labed (Journal of Applied Engineering Science and Technology, 2016)
This paper presents an experimental characterization on the mechanical behaviour offour different sandwich panels, for use in thermal insulation. These Panels are the results of thecombination of four composite materials; two materials as skins (Glass-Polyester and Plywood)and two as cores (Polystyrene and Cork agglomerate). From the comparison between themechanical behaviour of these four sandwich panels which was tested for three point-bendingtests; the sandwich with Glass-Polyester as skin and Cork agglomerate as core has the highestoverall stiffness compared to the other sandwich panels. Furthermore, thermal characteristics ofthese four panels (insulation materials) were numerically used in a comparative study of thermalperformances of solar flat plate collectors, FPCs. Thus, we have proceeded to the comparison ofthese FPCs efficiencies in order to determine the best performing model for agro-alimentary dryingapplications. From the comparison between these four FPCs, the highest efficiency was obtainedfrom the FPC insulation panel with plywood as skin and cork agglomerate as core.